Teks Taru Premana Sebagai Simbolisasi Ekuilibrium Manusia Hindu Dengan Alam Semesta Bali - Suka Ardiyasa, I Nyoman; Anggraini, Putu Maria Ratih (Jayapangus Press, 2024)
A holistic understanding of the side effects of chemical drugs, stimulating this era's humans to engage in contemplative movements, using ancient literature to maintain sanitation, physical health and mental health. Taru Premana is the philanthropic mission of Mpu Kuturan to create Hindu people as well as a healthy Bali environment. So, to realize the human mission, humanistic practice begins, to find a variety of herbal medicines. The research aims to analyze the Lontar Taru Premana, by looking for a link between health practices and the stimulation of subjects in the preservation of the environment. The research uses a qualitative approach or specifically applies textual studies to undermine searches and reconstructive efforts in understanding the texts of the art of traditional medicine of Bali. The technique of collecting Taru Premana manuscripts as a source of research data is obtained from the process of accumulating ancient writings dealing with traditional medicine. Further, it is analyzed using literary studies as well as philological studies. The compendium on traditional health science taught in Taru Premana is explained specifically in the processing techniques of traditional ingredients, their manufacturing processes and their application, such as bearing, spraying, patching and fixing. The Taru Premana manuscript has an interpretation in other aspects, namely as a symbolization of the internalization of the values of social-religious life. This lontar is an argument for the harmonization of man with his environment, and gives the scheme that man is not a determining entity, but an individual and a cosmic entity forming a typology of dependency. Taru Premana as a means of balancing the existence of humans and the environment (praja dan kamadhuk). In other words, man without the presence of nature is meaningless, because the process of life becomes stopped because of the nullity of the supporting life. Lontar Taru Premana plays an important role in the spiritual, social and ecological reality of the Bali Hindu community, as it applies traditional techniques and ecologic balance.